A Study on Feeds and Feeding Practices of Dairy Animals in Small Scale Farms of Kavre District, Nepal - Balami, Bhumika; Chaulagain, Rupendra (Nepalese Journal of Agricultural Sciences, 2025)
The study was conducted in selected wards of Panchkhal Municipality, Kavre, Nepal. A structural questionnaire was used to collect the primary information from the farm. The information collected were farm demographics, feeding practices, types of feed used, and the challenges encountered in ensuring adequate nutrition for their animals. The results revealed zero grazing, was the predominant farming method among dairy farmers in the area. Approximately 80-88% of the dairy animals raised were of crossbred type (79% Jersey cross and 8% Holstein Friesian cross). Dairy farmers primarily utilized locally available feed resources such as seasonal green grasses, forage crops, and crop residues, complemented by feedstuffs like broken rice, rice bran, wheat bran, rice polish, mustard cake, corn flour, molasses, salt, and thyme seeds. Mostly the feed was fed to the animals in the traditional method termed as “kudo” (meaning mixing of all available feed resources with water) to give to the productive animals. This study revealed that a total of 21 (51%) of respondents cultivated their fodder grass, with Napier grass (Pennisetum purpureum) being the most favored, followed by fodder oats (Avena sativa), and other grass varieties. About 33 (80.5%) of the farmers favored the artificial insemination (A.I) method, whereas 8 (19.51%) respondents opted for natural mating as their preferred breeding technique. The average milk yield per day was 10.26 liter. These findings provided valuable insights into the intricate challenges faced by regional dairy farmers, shedding light on their feeding practices, livestock management techniques, and the broader agricultural landscape.